Dynamic localization of glucokinase and its regulatory protein in hypothalamic tanycytes. - Magdiel Salgado; Estefanía Tarifeño-Saldivia; Patricio Ordenes; Carola Millán; María José Yañez; Paula Llanos; Marcos Villagra; Roberto Elizondo-Vega; Fernando Martínez; Francisco Nualart; Elena Uribe; María de Los Angeles García-Robles (PLoS ONE)
Glucokinase (GK), the hexokinase involved in glucose sensing in pancreatic β cells, is also expressed in hypothalamic tanycytes, which cover the ventricular walls of the basal hypothalamus and are implicated in an indirect control of neuronal activity by glucose. Previously, we demonstrated that GK was preferentially localized in tanycyte nuclei in euglycemic rats, which has been reported in hepatocytes and is suggestive of the presence of the GK regulatory protein, GKRP. In the present study, GK intracellular localization in hypothalamic and hepatic tissues of the same rats under several glycemic conditions was compared using confocal microscopy and Western blot analysis. In the hypothalamus, increased GK nuclear localization was observed in hyperglycemic conditions; however, it was primarily localized in the cytoplasm in hepatic tissue under the same conditions. Both GK and GKRP were next cloned from primary cultures of tanycytes. Expression of GK by Escherichia coli revealed a functional cooperative protein with a S0.5 of 10 mM. GKRP, expressed in Saccharomyces cerevisiae, inhibited GK activity in vitro with a Ki 0.2 µM. We also demonstrated increased nuclear reactivity of both GK and GKRP in response to high glucose concentrations in tanycyte cultures. These data were confirmed using Western blot analysis of nuclear extracts. Results indicate that GK undergoes short-term regulation by nuclear compartmentalization. Thus, in tanycytes, GK can act as a molecular switch to arrest cellular responses to increased glucose.